STUDI PELEPASAN IN VITRO KURKUMIN DARI NANOPARTIKEL KITOSAN DENGAN ASAM LAURAT SEBAGAI SURFAKTAN - , AGMAWARNIDA, Dr. Dwi Siswanta, M.Eng. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
A study on the release of curcumin from chitosan nanoparticles had been conducted in order to determine the effectiveness of the nanoparticles to release curcumin in dissolution media. The composition of the nanoparticles affected the release curcumin including chitosan, lauric acid with Hydrophile-Lipophile Balance 16 and glutaraldehid. Curcumin chitosan nanoparticles was prepared using solvent evaporation method by multiple emulsion. Nanoparticles were characterized using FT-IR Transmission Electron Microscopy (TEM) dan Scanning Electron Microscopy (SEM). The kinetics of the curcumin release were studied using several models